1776-1777, N.J. Laws 6 - (:unkn) unknown (My University, 1776)
"Act for the Inspection of Gunpowder," ch. 6, 1: Required the inspection of gunpowder prior to sale, and appointed state inspectors to "mark" lots that passed inspection.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER